Factors Affecting Organizational Citizenship Behavior (OCB) in Jambi Province Government Employees - Bambang Niko Pasla; Fathiyah Fathiyah (Jurnal Prajaiswara, 2021)
This study aimed to examine the Organizational Citizenship Behavior (OCB) of employees and the factors that influence it. The sample in this study was 120 employees of the Jambi Provincial Government. The data collection method used a questionnaire and was analyzed using verification analysis. The analytical tool in this study used Confirmatory Factor Analysis (CFA). The results of this study explain that OCB can be influenced by internal factors, namely job satisfaction, organizational commitment, employee morale, and work motivation, and external factors, namely leadership style and corporate culture, the highest and most influential factors in employee job satisfaction.